The Effectiveness of Comic Media in Improving Natural and Social Sciences (IPAS) Learning Outcomes - Puspita Lia Wijayani; M. Syahran Jailani; Donal Saputra (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to determine the effectiveness of using comic media in improving the cognitive learning outcomes of Natural and Social Sciences (IPAS) for fifth-grade students at Al-Munawwarah Private Madrasah Ibtidaiyah in Jambi City. This study uses a quantitative approach with a quasi-experimental research type and a nonequivalent control group design. The research subjects consisted of two classes, namely the experimental class, which applied IPAS learning using comic media, and the control class, which used conventional learning media. Data collection was carried out through pre-tests and post-tests, while data analysis used descriptive statistics, independent sample t-tests, and normalized gain (N-Gain) tests. The results showed that there was a significant difference in IPAS cognitive learning outcomes between the experimental class and the control class. The results of the independent sample t-test analysis showed a significance value (Sig. 2-tailed) of 0.30 < 0.05 and a t-value of 2.221, indicating a significant effect of the use of comic media on students' IPAS cognitive learning outcomes. The average N-Gain value of the experimental class was 0.60, which is in the moderate category, and the N-Gain effectiveness interpretation category was 60%, which is considered quite effective. Thus, comic media is effective in improving students' cognitive learning outcomes in IPAS, which can be used as an alternative innovative learning media to improve the quality of IPAS learning in Madrasah Ibtidaiyah.